ANALISIS PENGELOLAAN DANA DESA SEBAGAI REALISASI SALAH SATU TUJUAN PROGRAM NAWACITA “MEMBANGUN INDONESIA DARI PINGGIRAN” DI KECAMATAN BENER KABUPATEN PURWOREJO TAHUN 2016 - Ria Nurpuspita; Sudati Nur Sarfiah; Emma Dwi Ratnasari (Universitas Tidar, 2019)
The government implemented the Village Fund program in order to develop the economy of the small region. The allocation of village funds is expected to increase equitable development of village welfare through improving public services in the village, advancing the village economy, overcoming the development gap between villages and strengthening village communities as subjects of development. So in this study a research title is